# Simplify the expression and find its value when a = 5 and b = - 3

2(a^{2} + ab) + 3 - ab

**Solution:**

According to the question, the values of a = 5 and b = - 3.

Let us simplify the given expression 2(a^{2} + ab) + 3 – ab

In algebra we can add or subtract like terms, but unlike terms cannot be added or subtracted.

= 2(a^{2} + ab) + 3 – ab

= 2a^{2} + ab + 3

Now substituting the given values of a and b in 2a^{2} + ab + 3,

= 2 × 5 × 5 + 5 × (-3) + 3

= 50 - 15 + 3

= 38

**Video Solution:**

## Simplify the expression and find its value when a = 5 and b = - 3.

2(a² + ab) + 3 - ab

### Maths NCERT Solutions Class 7 - Chapter 12 Exercise 12.3 Question 10

**Summary:**

Simplifying the expression 2(a^{2} + ab) + 3 - ab when a = 5 and b = -3 we get the value as 38.